Ya llegamos a Amritsar (अमृतसर आ गया है) - Sahni, Bhishma; Thukral Kapoor, Uma (El Colegio de México, 2014)
Hindi to Spanish translation of Bhishma Sahni’s short story "Amritsar Āa Gayā Hai" अमृतसर आ गया है (The Train Has Reached Amritsar) by Uma Thukral Kapoor.